Le rôle de l’espace dans la littérature acadienne contemporaine Chacal, mon frère (2010) et L’Ombre de Chacal (2016) de Gracia Couturier - Żurawska, Anna (Romanica Silesiana, 2020)
The aim of deportation and expulsion of the Acadians during the so-called Grand Dérangement, also known as the Great Upheaval, was to deprive them of their land, which is presented in their history and literature. The idea of space is in this case closely connected with the question of identity in Acadian literature. Not referring directly to the above-mentioned historical events, Garcia Couturier explores in her novelistic diptych the relation between identity and space. Although Couturier’s writing is largely based on categories which characterise Acadian literature, she is able to go beyond them in order to concentrate on individual identity and liberty. She also investigates metaphorical expulsion, which shows her desire for autonomy from tradition and underlines modern aspects of the two novels. The aim of the article is therefore to examine the narrative representation of the space, its symbolic function and its role in shaping both individual and collective identity in Couturier’s novels.